An Amphiphilic Mesoporous Polymer Comprising a "built‐in" Imidazolium Ionic Liquid via Nanocasting Method as a Novel Catalyst Support with Combined Prospects. Issue 1 (8th January 2019) - Karimi, Babak; Artelli, Zahra; Mohammadi, Fariba; Mansouri, Fariborz; Hasannia, Maliheh; Marefat, Mohammad Reza; Vali, Hojatollah; Mastrorilli, Piero; Todisco, Stefano
Abstract: An imidazolium based ionic liquid bearing triethylene glycol (TEG) tag was employed as a functional monomer together with divinylbenzene to prepare a novel hydrophilic mesoporous polymer containing ionic liquid functionalities via nanocasting method using SBA‐15 as a hard template. The material was characterized using transmission electron microscopy (TEM), N2 sorption analysis, thermo‐gravimetric analysis (TGA), Fourier‐transform infrared spectroscopy (FT‐IR), elemental analysis (CHN), solid‐state NMR spectroscopy and contact angle measurement. It was found that the hydrophobic/hydrophilic properties of initial template, stepwise addition of monomers and initiator as well as amount of carrier solvent are of the important parameters in preparation of the polymer with uniform pore structure. Benefited from the combined properties such as incorporation of ionic liquid within the pore system of a flexible organic matrix together with its hydrophilic character, the material was found as an appropriate support to generate highly dispersed and very small size of Pd nanoparticles inside the pores. The prepared catalyst in this way, demonstrated outstanding activity, recyclability and high durability in the Suzuki cross‐coupling reaction of varied aryl halides with boronic acids in water as a green reaction medium. The beneficial role of imidazolium ionic liquid in the formation of small and highly active Pd nanoparticles was confirmed with comparative experiments. Abstract : Incorporation of a TEG substituted ionic liquid within the pore system of a flexible organic matrix together with its amphiphilic character provided highly dispersed and very small size of Pd nanoparticles inside the channels